Automatyzacja wzorcowania z zastosowaniem multi-produktowego kalibratora i testera = Automation of calibration using multi-product calibrator and tester - Belica, Daniel; Markiewicz, Jarosław; Nowakowski, Piotr; Szmytkiewicz, Adam; Tylkowski, Marcin; Olencki, Andrzej (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The concept of automating the calibration of measuring instruments for electrical quantities using a multi-product calibrator with automatic reading and recording of the calibrated device's readings and calculating the average value of the error and expanded measurement uncertainty was presented.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne